AI-assisted review of teaching competencies for comprehensive training of health professionals in Ecuador - Richard, Enrique (2024)
There is academic consensus that the curriculum should be taught by competencies. However, the teaching profile intended to teach them according to the different professional areas remains pending. So, what should be the ideal university teaching profile in the field of health sciences in Ecuador? And what competencies should I have regarding the substantive functions of university teaching? Consequently, we seek to outline an ideal teaching profile for university teaching in health sciences in Ecuador and list the minimum competencies necessary to fulfill its functions. A systematic review was carried out in academic search engines regarding the teaching profile by competencies for teaching in health sciences and the concept was worked on with artificial intelligence ©OpenAI. As a result of the review, a minimum of 83 competencies were found for the proposed teaching profile, of which 22 correspond to research, 28 to teaching, 15 to extension and 18 to management. None of them could be assigned as specific to the health area. A profile is proposed with emphasis on competencies inherent to biopsychosocial, bioethical aspects and skills resulting from professional practice. Finally, the work with OpenIA did show specific competencies linked to both bioethical aspects and specific and legal professional practice for Ecuador.